Business modeling and software design : 4th International Symposium, BMSD 2014, Luxembourg, Luxembourg, June 24-26, 2014, revised selected papers /: 4th International Symposium, BMSD 2014, Luxembourg, Luxembourg, June 24-26, 2014, revised selected papers. (2015) - Unknown
No abstract available